Becoming English: The Monro Family and Scottish Assimilation in Early-Modern England. (15th March 2019) - Brown, Keith; Kennedy, Allan
ABSTRACT: Migrant assimilation into host societies has been the subject of intense theoretical debate, but the applicability of the resultant modelling to historical data is unclear. This article addresses that lacuna through a case-study of the assimilation trajectory of one Scottish family, the Monros, in England in the century after 1690. The Monro experience suggests that 'classic' assimilation modelling remains a useful, if imperfect, conceptual tool. At the same time, it acts as a counter-point to historiographical narratives about the rise of 'Britishness', since the main loci of this family's identity were successively Scottish and English, but never 'British'.